Tanggungjawab perusahaan dalam investasi surat berharga syariah negara - Dewi Astutty Mochtar; Dewi Ayu Rahayu (University of Merdeka Malang, 2021)
This paper is motivated by the existence of new innovations in the world of capital markets and banking, namely an investment sukuk (state sharia securities) which is a bond investment based on sharia principles that can be issued by companies or governments. Sukuk investment is issued to finance the state budget, including the construction of a project. There are various types of sukuk investments because the contracts used when investing also vary. Every investment will certainly cause losses for the parties, so this will also be a loss for every investor who makes an investment, as well as sukuk investment, investors can also experience the risk of loss. Losses that can be experienced by each investor are different due to the different contracts in investing in sukuk. Loss experienced by investors is caused by negligence on the part of the management (company) then the company must be responsible for losses incurred due to negligence, the extent to which the company's responsibility depends on how much negligence the company did to cause losses to investors.How to cite item: Mochtar, D., Rahayu, D. (2021). Tanggungjawab perusahaan dalam investasi surat berharga syariah negara. Jurnal Cakrawala Hukum, 12(2), 150-158. doi:https://doi.org/10.26905/idjch.v12i2.6224